Complementary use of conduction system pacing techniques for the "pace and ablate" strategy in permanent atrial fibrillation - a case report - Catalin Pestrea; Roxana Enache; Ecaterina Cicala; Radu Vatasescu (Sciendo, 2024)
The feasibility of the conduction system pacing combined with atrioventricular node ablation was demonstrated in patients with atrial fibrillation in whom rate control can't be achieved with medication and heart failure.